The Other Side of the Coin Public Opinion toward Social Tax Expenditures. - Faricy, Christopher G. (Russell Sage Foundation, 2021)
"The United States provides economic security to citizens through a divided welfare state-one in which citizens receive benefits through both direct public programs and indirect tax subsidies. Studies of public opinion toward social policy have focused almost exclusively on direct programs; the purpose of this book is to understand public opinion toward tax expenditure programs-the "other side" of the American social welfare state. It examines how citizens form attitudes toward social tax expenditures, which not only are central to American economic security but also represent a significant portion of the federal budget, and how the design of social tax expenditure programs structure opinions toward social spending. The authors explore how social tax expenditures are expanding into new areas and might provide a way to expand the federal government's role in addressing the social problems caused by rising inequality and growing economic dislocation, while doing so in a way that is palatable to a public that is generally skeptical and distrusting of government"--